Assessing the value of volume navigation during ultrasound-guided radiofrequency- and microwave-ablations of liver lesions. (2021) - Meershoek, Philippa; van den Berg, Nynke S.; Lutjeboer, Jacob; Burgmans, Mark C.; van der Meer, Rutger W.; van Rijswijk, Catharina S.P.; van Oosterom, Matthias N.; van Erkel, Arian R.; van Leeuwen, Fijs W.B.
Abstract: Purpose: The goal of our study was to determine the influence of ultrasound (US)-coupled volume navigation on the use of computed tomography (CT) during minimally-invasive radiofrequency and microwave ablation procedures of liver lesions. Method: Twenty-five patients with 40 liver lesions of different histological origin were retrospectively analysed. Lesions were ablated following standard protocol, using 1) conventional US-guidance, 2) manual registered volume navigation ( m VNav), 3) automatic registered ( a VNav) or 4) CT-guidance. In case of ultrasonographically inconspicuous lesions, conventional US-guidance was abandoned and m VNav was used. If m VNav was also unsuccessful, the procedure was either continued with a VNav or CT-guidance. The number, size and location of the lesions targeted using the different approaches were documented. Results: Of the 40 lesions, sixteen (40.0 %) could be targeted with conventional US-guidance only, sixteen (40.0 %) with m VNav, three (7.5 %) with a VNav and five (12.5 %) only through the use of CT-guidance. Of the three alternatives ( m VNav, a VNav and CT only) the mean size of the lesions targeted using m VNav (9.1 ± 4.6 mm) was significantly smaller from those targeted using US-guidance only (20.4 ± 9.4 mm; p < 0.001). The location of the lesions did not influence the selection of the modality used to guide the ablation. Conclusions: In our cohort, m VNav allowed the ablation procedure to become less dependent on the use of CT. m VNav supported the ablation of lesions smaller than those that could be ablated with US only and doubled the application of minimally-invasive US-guided ablations.